TROMBICULOSIS IN CATS DUE TO NEOTROMBICULA AUTUMNALIS (ACARI: TROMBICULIDAE) LARVAE: THE FIRST REPORT IN ROMANIA - P. Tudor; C. Fernoaga; N. Tudor (Journal of Animal and Plant Sciences, 2015)
Neotrombicula autumnalis is an arthropod that parasitises cats during the larval stage and induces pruritic dermatitis described as trombiculosis. This report describes the infestation of two cats with N. autumnalis mite larvae. Physical examination of both cats revealed cutaneous lesions on the ears, limbs (elbow, interdigital spaces) and around the nipples represented by erythema, papules, crusts and pruritus. Microscopic examination of skin scrapings revealed N. autumnalis larvae in both cats. To our knowledge, this is the first report of N. autumnalis larvae infestation in cats from Romania.
Keywords: cats; Neotrombicula autumnalis; trombiculosis